Current trends, applications, and challenges of coatings on additive manufacturing based biopolymers: A state of art review. Issue 10 (16th June 2022) - Sharma, Shrutika; Gupta, Vishal; Mudgal, Deepa
Abstract: Healing of bone fractures highly depends on the biocompatibility, stability in biological conditions, biodegradability, technical functionality, and shelf‐life of biomaterials. Metallic biomaterials offer excellent mechanical properties and biocompatibility. However, metallic bone implants result in stress shielding, release of toxic ions, excessive wear, and corrosion. Polymer materials are being explored for bone implants due to their light‐weight, biocompatibility, biodegradability, and absence of stress shielding. In the new era, additive manufacturing (AM) is being preferred due to its capability of fabricating customer specific implants with minimum material wastage. However, AM based polymer implants lack in mechanical strength and biological properties. Surface modification of polymeric substrates using coatings and incorporation of bioadditives have been regarded as alternatives for improvement of mechanical and biological properties. This review discusses about various coating techniques and gives an overview about coatings and bioadditives that can be used for enhancement of properties. From the review, it is evident that reinforcement of hydroxyapatite to polylactic acid resulted in prevention of crack growth during shape recovery cycles which can be used for self‐fitting implants. Coatings have been successful in enhancing hydrophilicity, mechanical properties, anti‐biofouling, antibacterial and anti‐coagulative properties, adhesion, proliferation, and differentiation of cells on the coated surface. This review also discusses the challenges that need to be overcome for progression in this field. Abstract : Surface modification of polymeric substrates using coatings and incorporation of bioadditives has been regarded as alternatives for improvement of mechanical and biological properties. This review discusses about various coating techniques and gives an overview about coatings and bioadditives that can be used for enhancement of properties. This review also discusses the challenges that need to be overcome for progression in this field.